MACROSCOPIC AND MICROSCOPIC CHANGES IN THE RESPIRATORY SYSTEM OF BALI DUCKS AFTER INFECTION WITH THE VIRULENT NEWCASTLE DISEASE VIRUS - Baiti, Nur; Winaya, Ida Bagus Oka; Adi, Anak Agung Ayu Mirah (Buletin Veteriner Udayana, 2023)
This study aims to determine the macroscopic and microscopic changes in the respiratory system of bali ducks after infection with the virulent Newcastle Disease (ND) virus. This study used Bali ducks aged 1 week as many as 15 ducklings were divided into 2 treatments randomly. P 0 was used as a control treatment which was given intraocular PBS 0,5 ml, while P 1 was infected with the virulent virus isolate Tabanan1/ARP/17. One day before virus inoculation, blood was taken from the jugular vein of Bali ducks for antibody titer measurement. After the acclimatization process was completed, Bali ducks were inoculated with avian orthoavulavirus (AOAV) at a dose of 2 7 HA units of 0,5 ml intraocularly. Ducks that died after ND virus infection were necropsied, the organs of the larynx, trachea and lungs were observed for anatomical changes, then tissue samples were taken and put into Neutral Buffer Formaline 10%. Ducks P 0 and P 1 that had not died on day 30 after infection were euthanized and then necropsied. Tissue samples were processed and stained with Hematoxylin Eosin staining. The results of macroscopic observation of the trachea and lungs showed hemorrhage. Histopathological lesions were observed under a microscope and the results were presented descriptively, the results showed that the Tabanan1/ARP/17 isolate AOAV-1 virus caused histopathological lesions in the form of congestion, hemorrhage, edema, and inflammatory cell infiltration in the lungs, trachea and larynx. . Macroscopic and microscopic changes in the respiratory system of bali ducks infected with the virulent ND virus were associated with age, virus distribution, viral stain and factors that influenced the macroscopic and microscopic changes caused.